1971
DOI: 10.1136/bmj.4.5781.217
|View full text |Cite
|
Sign up to set email alerts
|

Chorea and the Oral Contraceptives

Abstract: SummaryThe case histories are reported of six women who developed chorea while taking oral contraceptive drugs. The chorea that results from taking compounds containing oestrogen and progestogen has many features in common with chorea gravidarum, and the pathogenesis is probably similar. In some of the patients, however, the sudden onset of symptoms suggests a vascular aetiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Results consistent with both reduction and increase of striatal dopaminergic function by estradiol have been reported for all indices of dopaminergic activity, including receptor levels/binding, membrane dopamine transporter levels, and release, depending on dose and treatment paradigm (Arvin et al, 2000;Bazzett and Becker, 1994;Becker and Beer, 1986;Becker and Rudick, 1999;Di Paolo, 1994, 1982, 1984, 1985Disshon et al, 1998;Disshon and Dluzen, 2000;Dluzen, 1997;Landry et al, 2002;McDermott, 1993;McDermott et al, 1994;Morissette et al, 2008;Morissette and Di Paolo, 1993;Peris et al, 1991;Shieh and Yang, 2008;Thompson and Moss, 1994;Zhou et al, 2002). It has been suggested that antidopaminergic effects are primarily exerted by high doses of estrogen or chronic administration, whereas pro-dopaminergic actions are more associated with lower physiological levels of estrogen (Barber et al, 1976;Becker, 1999;Bedard et al, 1977;Cyr et al, 2002;Di Paolo, 1994;Di Paolo et al, 1981;Hruska and Silbergeld, 1980;McEwen and Alves, 1999;Riddoch et al, 1971). The specific mechanisms by which estradiol exerts the effects observed here remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Results consistent with both reduction and increase of striatal dopaminergic function by estradiol have been reported for all indices of dopaminergic activity, including receptor levels/binding, membrane dopamine transporter levels, and release, depending on dose and treatment paradigm (Arvin et al, 2000;Bazzett and Becker, 1994;Becker and Beer, 1986;Becker and Rudick, 1999;Di Paolo, 1994, 1982, 1984, 1985Disshon et al, 1998;Disshon and Dluzen, 2000;Dluzen, 1997;Landry et al, 2002;McDermott, 1993;McDermott et al, 1994;Morissette et al, 2008;Morissette and Di Paolo, 1993;Peris et al, 1991;Shieh and Yang, 2008;Thompson and Moss, 1994;Zhou et al, 2002). It has been suggested that antidopaminergic effects are primarily exerted by high doses of estrogen or chronic administration, whereas pro-dopaminergic actions are more associated with lower physiological levels of estrogen (Barber et al, 1976;Becker, 1999;Bedard et al, 1977;Cyr et al, 2002;Di Paolo, 1994;Di Paolo et al, 1981;Hruska and Silbergeld, 1980;McEwen and Alves, 1999;Riddoch et al, 1971). The specific mechanisms by which estradiol exerts the effects observed here remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively high levels of estrogens, including oral contraceptives and estrogen replacement therapy, exacerbate symptoms of Parkinson's disease (6,249,250), pointing to antidopaminergic actions that are opposite to the actions of physiological levels of estradiol. A similar antagonistic effect of chronic or high-dose estrogen was found in male and female rats for drug-induced motor activity (251,252).…”
Section: Catecholaminergic Neuronsmentioning
confidence: 99%
“…The efficacy of the antibiotics used in secondary prophylaxis may be limited due to the uncertain quality of some products; 4. Other non-rheumatic causes of chorea, such as viral infections, tumors of the central nervous system, degenerative processes, among others, [18][19][20][21] have to be considered. This is especially so for those patients who present with recurrent isolated chorea while on adequate prophylaxis.…”
mentioning
confidence: 99%